Comparative Analysis of Graphitization Characteristics in Bamboo and Oak Charcoals for Secondary Battery Anodes - Kiseon Lee; Seung-Kon Ryu; Hong-Gun Kim; Lee-Ku Kwac; Young-Soon Kim (Crystals)
When compared to natural graphite, artificial graphite has advantages such a longer cycle life, faster charging rates, and better performance. However, the process of producing it, which frequently uses coal, raises questions about the impact on the environment and the depletion of resources. Eco-friendly, wood-based graphite must be developed in order to solve these problems. This study assessed and investigated the characteristics of charcoals derived from bamboo and oak which were utilized to produce graphite. After heating to 1500 °C at 10 K/min, 86.87 wt% of oak charcoal and 88.33 wt% of bamboo charcoal remained, indicating a yield of more than 85% when charcoal was graphitized. Depending on the species of wood, different-sized pores showed different shapes as the graphitization process advanced, as revealed by SEM surface analyses. The carbon atoms seen in the XRD crystal development changed into graphite crystals when heated to 2400 °C, and the isotropic peaks vanished. Bamboo charcoal has a higher degree of crystallinity than other wood-based charcoals, such as oak charcoal, which is made up of turbostratic graphite, according to Raman spectroscopic research. Lithium-ion batteries employ bamboo charcoal as their anode material. At this point, the values for soft carbon were determined to be 196 mAh/g and for hard carbon to be 168 mAh/g at a current density of 0.02 A/g.